400 years of the hospital Simón Ruiz (1619-2019). Medical-social aspects (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
The Simón Ruiz Hospital of the town of Medina del Campo began its operation at the beginning of the 17th century and had been built and financed by the banker who bears his name. Its construction was done according to new patterns and concepts getting a sober but majestic building. It has been written in a very extensive way about the aspects of its architectural profiles, but there are others little treated, linked to its operation and how this was changing over time; according to a society that also experienced evolutionary processes. This is the aspect that is most considered in this paper.
Keywords: : Simón Ruiz Hospital; Medina del Campo; history; medical-social.